Academic Writing Students’ Perceptions on Teacher Feedback - Zipora Haniel Kileri; Listyani Listyani (Universitas Muria Kudus, 2021)
Academic Writing is a difficult subject for many students because the content requires highly critical academic thinking. Students have to put their ideas to build up arguments. Teachers’ role is very important here in giving direct and indirect feedback to help students solve problems in their essays. Students’ perceptions of teacher feedback in Academic Writing class is the central focus of this paper. The purpose of the study is to describe Academic Writing students' perceptions of teacher feedback. Data were taken through interviews with six students of the English Language Education Study Program (ELEP), of the Faculty of Language and Arts (FLA) in a private university, in Central Java, Indonesia. They had passed the Academic Writing course at the time the interviews were conducted. The kind of interview that was used in this study is a semi-structured interview. Results showed that some students had positive perceptions of teacher feedback, while some others showed negative perceptions. The results of this study hopefully can be useful for Academic Writing lecturers to know more about what kind of feedback is best to be given to their students, adjusted with their needs.